Vitiligo: Clinical Implications and Cell Line Models for Formulation Evaluation (Asian Journal of Pharmaceutics (AJP), 2025)
A chronic autoimmune disorder called vitiligo, with a prevalence rate of 0.004–2.28, is encouraged worldwideand is characterized by increasing skin pigmentation loss due to melanocyte destruction, resulting in depigmentedskin patches. There are two primary categories of this condition: Segmental Vitiligo (SV), which is less prevalentand usually only affects one side of the body, and Non-SV, the most pervasive form and frequently associatedwith other autoimmune disorders. An autoimmune reaction that targets melanocytes is the outcome of the delicateinteraction between genetic susceptibility and environmental variables in the pathophysiology of vitiligo. Theclinical evaluation and family history are the basis for the diagnosis, which might additionally include skin biopsiesand blood tests for assessing melanocyte loss. Vitiligo has a major psychological influence on one’s quality ofliving and can cause problems, including fret, low self-esteem, and social stigma. This summary highlights thenecessity of having a thorough awareness of vitiligo to enhance management techniques and assist those suffering.